QUALITY PRESCHOOL SERVICES BASED ON PARENT PARTNERSHIP AT AR RAYYAN PAUD PARUNG BOGOR - Anita; Setiowati, Ike; Yeny; Apriani, Dede; Tazkiah, Nita; Puridawaty, Brigita (International Conferences on Early Childhood Education Proceedings, 2024)
Parents are the main and first educators for early childhood since the child was born. The role of parents is very important in stimulating all aspects of development in their golden years. PAUD is a child's first step in the world of education and the starting point of their journey in developing and playing a role in society. One of the elements of Quality PAUD is a partnership with parents in accordance with Minister of Education and Culture Regulation Number 30 of 2017 concerning Family Involvement in the Implementation of Education, as well as Directorate General Regulation Number 127 2017 concerning Guidelines for Implementing Family Involvement in the Implementation of Education in PAUD, namely as a process and/or way for families to participate in the implementation of education in order to achieve national education goals. The method in this research is a survey method and the results of the research show that quality PAUD services based on parent partnership at Ar Rayyan PAUD are 8.7 doubtful, 32.9 satisfied, and 58.4 very satisfied. These results show that parents' satisfaction in partnering with schools is a reflection of quality PAUD services at Ar Rayyan PAUD.